Molecular Dynamic and Docking Simulation to Prevent Thymine Dimer as the Main Reason for Skin Cancer - (:unkn) unknown (AMG Transcend Association, 2021)
Two major types can be repaired UV-induced DNA lesions. The first one is a light-dependent process that reverts UV damage applying particular wavelengths. The second is a light-independent process that excises the light-damaged region under novo synthesis of an intact DNA. The iGEMDOCK has been used for this study, and the acceptable thymine dimer can be defined for the binding site in whole DNA structures. The DNA is worked with two thymine in a segment of nucleic acids, and iGEMDOCK can help to prepare a suitable binding between them. The total energies of the model systems are a total of several partial energies as follows: E(system) = E(bond) + E(angle) + E(torsion) +E(over) +E(vdW) + E(Coulomb) + E(Specific). EvdW +E(Coulomb) represents the dispersive and electrostatic energies contribution between all atoms, respectively. Finally, E(Specific) is system-specific energy such as lone-pair, conjugation, and hydrogen binding. The DFT and HF calculations of the thymine dimer exhibited that the ring fusion at the C5 and C6 atoms of two thymine bases produced a four-member cyclo-butane puckered ring, as well as the feature, is seen with the MPn or Moller-Pleset level. In addition, the UV radiations between 360 nm to 200 nm have been investigated for the study of thymine dimers.